2014
DOI: 10.1111/gcb.12758
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in predicting rice yield by current crop models under a wide range of climatic conditions

Abstract: Predicting rice (Oryza sativa) productivity under future climates is important for global food security. Ecophysiological crop models in combination with climate model outputs are commonly used in yield prediction, but uncertainties associated with crop models remain largely unquantified. We evaluated 13 rice models against multi-year experimental yield data at four sites with diverse climatic conditions in Asia and examined whether different modeling approaches on major physiological processes attribute to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
286
3
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 380 publications
(311 citation statements)
references
References 38 publications
17
286
3
5
Order By: Relevance
“…Many MME studies with crop models have remarked that the mean or median of the simulated values seems to give good agreement with observed yields (Asseng et al 2014;Bassu et al 2014;Li et al 2015;Palosuo et al 2011). Martre et al (2015) found that when multiple outputs are considered, the mean and median were both better predictors than even the best individual model, with the median being slightly better than the mean.…”
Section: Using the Ensemble Average As Estimator Or Predictormentioning
confidence: 87%
See 3 more Smart Citations
“…Many MME studies with crop models have remarked that the mean or median of the simulated values seems to give good agreement with observed yields (Asseng et al 2014;Bassu et al 2014;Li et al 2015;Palosuo et al 2011). Martre et al (2015) found that when multiple outputs are considered, the mean and median were both better predictors than even the best individual model, with the median being slightly better than the mean.…”
Section: Using the Ensemble Average As Estimator Or Predictormentioning
confidence: 87%
“…One approach with crop models has been to identify models that have similar equations for underlying processes, such as photosynthesis. In general, however, it has not been found that structural similarity leads to similarity in simulated values in crop MMEs (Palosuo et al 2011;Martre et al 2015;Li et al 2015). An alternative approach, proposed for climate models (Bishop and Abramowitz 2013), is to examine the covariance in model errors as the measure of model dependence.…”
Section: Evaluating the Degree Of Relatedness Of The Models In A Mmementioning
confidence: 98%
See 2 more Smart Citations
“…This has urged for benchmarking actions at an international level, where estimation of processoriented epistemic uncertainties is done by running several models supposed to simulate the same reality (ensemble modelling) so as to generate an expanded envelope of uncertainty (Asseng et al, 2013;Bassu et al, 2014;Li et al, 2014). We address the same issues with grassland ecosystems in Europe and Israel, with focus on permanent, semi-natural or sown grasslands under management for at least 5 years, composed of multiple plant species.…”
Section: Introductionmentioning
confidence: 99%